Autotaxin, bile acid profile and effect of ileal bile acid transporter inhibition in primary biliary cholangitis patients with pruritus. (25th February 2019) - Hegade, Vinod S.; Pechlivanis, Alexandros; McDonald, Julie A. K.; Rees, Douglas; Corrigan, Margaret; Hirschfield, Gideon M.; Taylor‐Robinson, Simon D.; Holmes, Elaine; Marchesi, Julian R.; Kendrick, Stuart; Jones, David E.
Abstract: Background and Aims: Pruritus is a common symptom in patients with primary biliary cholangitis (PBC) for which ileal bile acid transporter (IBAT) inhibition is emerging as a potential therapy. We explored the serum metabonome and gut microbiota profile in PBC patients with pruritus and investigated the effect of GSK2330672, an IBAT inhibitor. Methods: We studied fasting serum bile acids (BAs), autotaxin and faecal microbiota in 22 PBC patients with pruritus at baseline and after 2 weeks of GSK2330672 treatment. Control group included 31 asymptomatic PBC patients and 18 healthy volunteers. BA profiling was done by ultra performance liquid chromatography coupled to a mass spectrometry (UPLC‐MS). Faecal microbiomes were analysed by 16S ribosomal RNA gene sequencing. Results: In PBC patients with pruritus, serum levels of total and glyco‐conjugated primary BAs and autotaxin were significantly elevated. Autotaxin activity correlated significantly with tauro‐ and glyco‐conjugated cholic acid (CA) and chenodeoxycholic acid (CDCA), both at baseline and after GSK2330672. GSK2330672 significantly reduced autotaxin and all tauro‐ and glyco‐ conjugated BAs and increased faecal levels of CA ( P  = 0.048) and CDCA ( P  = 0.027). Gut microbiota of PBC patients with pruritus was similar to control groups. GSK2330672 increased the relative abundance of Firmicutes ( P  = 0.033) and Clostridia ( P  = 0.04) and decreased Bacteroidetes ( P  = 0.033) and Bacteroidia ( P  = 0.04). Conclusions: Pruritus in PBC does not show a distinct gut bacterial profile but is associated with elevated serum bile acid and autotaxin levels which decrease after IBAT inhibition. In cholestatic pruritus, a complex interplay between BAs and autotaxin is likely and may be modified by IBAT inhibition.